Overcoming challenges and achieving high HPV vaccination uptake in Cameroon: lessons learned from a gender-neutral and single-dose program and community engagement - Andreas Ateke Njoh; Dur-E-Nayab Waheed; Tchokfe Shalom Ndoula Josue Kedakse; Lionel Junior Ebongue; Eugene Justine Kongnyuy; Adidja Amani; Afizu Chrakoh Tambasho; Yauba Saidu; Mohamed II Kaba; Clovis Nchinjoh Sangwe; Herman Kenfack; Judith Seungue; et al. (BMC Public Health)
Abstract Introduction Human papillomavirus (HPV) is sexually transmissible and affects almost all sexually active people. The virus infects females and males, causing genital warts, cervical cancer, and oropharyngeal cancers in some. The disease burden is highest in resource-constrained countries, and it is a leading cause of cancer-related mortality in Cameroon. HPV infection is preventable by vaccination. Despite the merits of HPV vaccination, improving coverage has remained difficult in Cameroon. This paper highlights the challenges, lessons learned, and progress in HPV vaccination as part of Cameroon’s gender-neutral-single-dose approach and the periodic intensification of routine immunization (PIRI). Methods This ecological cross-sectional study, conducted from July to December 2023, examines the introduction of the HPV vaccine in Cameroon, along with associated challenges, strategies, and progress. Vaccination data from 2020 to 2023 were retrieved from Cameroon’s District Health Information Software (DHIS2), while information on the vaccine introduction process and challenges was sourced from Expanded Programme on Immunisation (EPI) reports. Data analysis was performed using Python. The Shapiro–Wilk test assessed normality, and segmented regression analysis within an interrupted time series framework was applied to evaluate the contribution of each intervention to HPV vaccination uptake among girls. Statistical significance was set at a 95% confidence interval (CI) with a p-value < 0.05. Microsoft Excel 365 was used for calculating vaccination coverage proportions and visualizing results through figures and tables. Results Cameroon introduced the HPV vaccine to nine-year-old girls in October 2020 amidst negative rumours. The first dose coverage stayed around 20% for three years. Following the National Immunization Technical Advisory Group recommendation, the Ministry of Health intensified communication and community engagement, switched to a single-dose vaccination for nine-year-old boys and girls in January 2023, and PIRI in households and schools in March 2023. All regions improved, with four (Adamawa, East, Far North, and North) having coverages for girls over 90% and around 40% for boys. National-level vaccination coverage for girls improved three-fold, and boys recorded 26%. Interrupted time series highlighted an immediate improvement in girls’ vaccination following PIRI in 70% of regions and nationally. In contrast gender-neutral-single-dose vaccination led to immediate improvement in coverage in 30% of regions (Far North, South, South West) and at the national level, while intensified communication lacked significant contribution. Conclusion HPV vaccination in Cameroon has faced significant challenges. However, interventions such as adopting a gender-neutral, single-dose policy and implementing PIRI have greatly improved coverage across various levels of the health system since 2023.